In Memory of Ion Vaduva (Analele Universității București. Informatică, 2024)
We will make a presentation of the life and activity of former University Professor Dr. Ion Văduva, from the Faculty of Mathematics and Computer Science of the University of Bucharest. I met the professor as supervisor of my doctoral thesis, as a participant in various scientific events (conferences, summer schools, etc.), as a collaborator in research contracts, and as an invitee to activities and events held at the University from Craiova. On November 17, 2017, our university awarded him the title of Doctor Honoris Causa. As the organizer of this event, I had long discussions regarding the biography and activity of the professor; additionally, he has provided me with materials in this regard. All this allowed me to prepare this article.